Samoans to profit from local tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
A product derived from a Samoan tree is showing promise as an HIV/AIDS drug, and islanders will get half of the profits from its sale if clinical trials, already under way, prove successful.